Variação de formas de crescimento de Montastraea cavernosa (Linnaeus, 1767) (Cnidaria, Anthozoa, Scleractinia): uma abordagem modular - Barbeitos, Marcos Soares (2000)
Clonal animals grow through addition of functional units (zooids), whose assemblage constitutes a colony. The modular approach consists in describing colony form from the arrangement and size of modules. The modular approach was used here to access variations in growth forms of the coral Montastraea cavernosa using the arrangement and the size of polyps in the inner face of the colonial of 46 samples collected in Parcel das Paredes (BA) and João Pessoa (PB). Results showed that area of the polyps is partially explained by factors related to the spacing among them. These factors vary with the form of the colony and with the range of polyp sizes being analyzed. A hypothetical conceptual model for the relationship among colonial growth forms, polyp sizes and organization is proposed. Possible evolutionary reasons for such a model are discussed as well as possible implications to morphometric studies of this species.